Perbandingan Implementasi Kurikulum 2013 Dengan Kurikulum International Baccalaureate (Kajian Pada Mata Pelajaran Bahasa Indonesia) - Fika Tresnawati; Enung Nurhayati (FKIP, Universitas Palangka Raya, 2023)
Based on public opinion which states that the international curriculum is better than the national curriculum, so many parents pay more to send their children to private schools with international labels even though they have to spend a lot of money. This is caused by the presence of several factors into consideration for parents. For example, student learning factors that put them into various exams and memorization system, while in the international curriculum at the elementary level, students are more emphasized on a deep understanding of the phenomena and lessons that students want to know without worrying about the final result in the form of grades. That is why the government is trying to fix the world of education by changing the curriculum system from KTSP to the 2013 Curriculum, where the 2013 curriculum system has several things that are considered to slightly adopt the existing system in the international curriculum. Based on this, the author wants to find out more about the differences and agreements between the 2013 Curriculum and the IB Curriculum. This study uses a comparative descriptive method with a qualitative approach. This study aims to describe the differences and similarities between the National Curriculum (2013) and the International Curriculum (IB-PYP). The results of the study showed that there were significant differences between the two curricula. Where the National Curriculum (2013) places more emphasis on the content of lessons and final results, while the International Curriculum (IB-PYP) places more emphasis on student character towards the process and understanding of each subject.